INDUSTRY OF THE REPUBLIC OFUZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Igor Chekulay Vladimirovich; G’oyibnazarova Oygul Olloqul qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: this article discusses the industry of the Republic of Uzbekistan and its significant contribution to the country’s economic development. It explains how various sectors of industry have undergone important modernization, technological renewal, and structural reforms to strengthen the national economy, increase production capacity, and improve the quality of life. The article highlights the achievements in key industrial branches such as energy, mining, metallurgy, oil and gas, and textile production, which serve as the backbone of Uzbekistan’s industrial growth and economic stability. It also emphasizes the extensive reforms carried out in recent years to attract foreign investment, expand international cooperation, and introduce modern technologies into industrial processes.The article additionally outlines progress in important areas such as manufacturing, construction materials, chemical production, and the automotive industry. It describes efforts to develop industrial infrastructure, establish free economic zones, support entrepreneurship, and promote innovation and digital technologies. These measures have helped diversify the economy, increase export potential, and enhance the competitiveness of national products in global markets. Overall, the article shows how Uzbekistan’s rapidly developing industry—through modernization, investment, and innovation—has contributed to building a strong and sustainable economy that successfully combines traditional sectors with modern industrial growth.